Universal Pre-School and Labor Supply of Mothers - Mike Brewer; Sarah Cattan (ifo DICE Report, 2017)
Expanding access to pre-school education and childcare services has been a key policy on the agenda of many governments for over 30 years. Several motivations have been at the heart of these policies. On the one hand, expanding access to quality pre-school education is expected to have positive effects on child development and reduce socio-economic inequalities in life chances by providing a nurturing and stimulating environment to all children. On the other hand, an increased availability of affordable pre-school services is also hoped to raise maternal employment, which in turn could promote gender equality, reduce poverty, foster economic growth and increase the tax base. By making it easier to reconcile work and family responsibilities, the provision of childcare services might also help to increase fertility, which could contribute to relieving pressures created by ageing populations. A large and robust literature that looks carefully at various policies implemented over the past 30 years provides important insights into the link between universal pre-school and maternal labour supply. It shows that universal pre-school childcare is not always a panacea; instead, the impact of these policies has been very mixed. In what follows, we summarise this evidence, discuss why it is so mixed, and ask whether lessons can be learned to make future policies more effective.
Keywords: J13; J16; J18; J22; 330; Arbeitsangebot; Mütter; Kinderbetreuung; Kinderbetreuungseinrichtung; Familie-Beruf